Human Security in South Asia: Lesson for Nepal - Adhikari, Naresh Bhakta (BMC Research Journal, 2025)
The concept of human security has evolved beyond traditional state-centric approaches to encompass the protection of individuals from a range of threats, including economic instability, environmental degradation, and political insecurity. South Asia, characterized by significant human security challenges such as poverty, armed insurgencies, environmental vulnerabilities, and governance deficits, presents a critical case for examining the complexities of human security. This study employs a qualitative research methodology, utilizing secondary data sources, to explore the status, challenges, and prospects of human security in South Asia, with a focus on deriving lessons for Nepal. The study highlights the interconnected nature of threats within the region by drawing on frameworks such as the UNDP's multidimensional concept of human security, Amartya Sen’s Human Development Theory, and Barry Buzan’s Regional Security Complex Theory. Common issues such as political instability, environmental insecurity, and forced migration exacerbate human insecurity, further complicated by traditional security concerns like border disputes and transnational terrorism. For Nepal, lessons emerge from addressing systemic inequalities, strengthening governance, and adopting people-centered development approaches. This analysis underscores the urgency of regional cooperation and integrated strategies to mitigate human insecurity and foster sustainable development in South Asia.